Indications and pregnancy outcomes when multidisciplinary centers for prenatal diagnosis refuse request for termination of pregnancy: a retrospective French study. (20th March 2013) - Nguyen, M. L.; Roman, H.; Dommergues, M.; Verspyck, E.
ABSTRACT Objectives To report indications and risk factors for effective termination of pregnancy (TOP) when multidisciplinary prenatal diagnosis centers refuse request for TOP. Methods This is a retrospective study from a French national registry between 2005 and 2009. Indication groups for TOP refusal were created. Risk factors for pregnancy outcomes and effective TOP were determined by multinomial logistic regression model. Results The overall number of TOP refusals was 573. Indications were single malformations (37%), chromosomal abnormalities (16.6%), hygroma (5.2%), potential fetopathies (11%), maternal indications (17.4%), and other indications (12.7%). Pregnancy outcomes were live infants (35.1%), effective TOP (36.3%), intra‐uterine fetal death (5.4%), and lost to follow‐up (23.2%). Logistic regression model showed an increased likelihood of effective TOP in groups with single malformations [odds ratio (OR) 3.4, 95% confidence interval (CI) 1.6–7.4], chromosomal abnormalities (OR 3, 95% CI 1.2–7.2), and hygromas (OR 19.6, 95% CI 2.3–16.8) compared with other groups. An increased likelihood of effective TOP was also reported when the request was made at first (OR 29.5, 95% CI 10–16.7) and second (OR 6.3, 95% CI 2.3–16.7) trimesters compared with the third trimester. Conclusions Effective TOP is particularly frequent when requested during the first trimester and in cases of structural anomalies of the fetus. © 2013 John Wiley & Sons, Ltd.